Analisis Peran Kurikulum Penjas Masa Depan Dalam Membentuk Keterampilan Era Abad 21 - Neng Titih; Dikdik Fauzi Dermawan; Mutiara Rahma Asri Pratami; Irfan Zinat Achmad (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this reserch is to find out the role of the future Physial Education curriculum in forming 21st century skilss. The method used in this article is the library method with a descriptive approach. The results of the discussion in this article show that the role o the future physical education curiculum is very important for the development of 21st Century skilss, because physical education only allows student with a high proportion of physical activity to achieve general educational goals. The curriculum does not only discuss movement skills and physical health, but students are required to become critical, creative and collaborative thinkers. The 21st century physical education curriculum is the most visible change in physical education. Education is not only about sports games, but must provide learning resources from modern technology packages. Therefore, the physical education curriculum is structured to produce people who have good health and skills for the global challenges of the 21st century. In addition, professional PJOK teachers are needed to understand and apply the Physical Education curriculum.